DABIGATRAN ETEXILATE FOR PREVENTION OF CARDIOEMBOLIC COMPLICATIONS IN NONVALVULAR ATRIAL FIBRILLATION: HOW TO DO THE INTERVENTION MORE EFFECTIVE AND SAFER - I. S. Yavelov (Рациональная фармакотерапия в кардиологии, 2016)
Application of dabigatran etexilate for prevention of cardioembolic complications in nonvalvular atrial fibrillation is considered. Results of randomized clinical trials on efficacy and safety of dabigatran in various doses are discussed. Besides, a comparison of dabigatran and varfarin therapies is presented taking into account pharmacoeconomic data. Recommendations on dabigatran dosing are considered to do intervention more effective and safer.